Knowledge and associated factors towards post-operative pain management among nurses working at referral hospitals, Ethiopia - Desalegn Tariku Jaleta; Techane Sisay Tuji; Addisu Dabi Wake (Open Journal of Pain Medicine - Peertechz Publications, 2021)
Introduction: Post-Operative Pain (POP) is a common patient problem subsequently surgical procedure. Uncontrolled POP reduces physical, social and overall recovery of the patient. Effective pain management requires faultless knowledge.  Objective: To determine Knowledge and its associated factors towards POP management among nurses working in referral hospitals, northwest Ethiopia.  Methods: Data were collected from Nurses from March 08 to April 23, 2019. Nurses who are working in the surgical track were included in the study. The data were analyzed by SPSS version 20 Software.  Result: The nurses' level of good knowlegde towards POP management was 43.46%. The multivariable logistic regression analysis showed; master of science degree (AOR=3.125, 95%CI (2.53-10.11)], bachelor of science degree [(AOR=2.10,95%CI (1.86, 9.05), having 5 to10 years working experience [(AOR= 2.661, 95%CI (1.278, 5.540), having 10 to 15 years of working experience [(AOR= 2.581 95%CI (1.758, 11.938)], having 15 to 20 years working experience [AOR=4.62,95%CI (1.28, 6.68), having >20 years of working experience [AOR=7.27,95%CI (1.44, 11.95), receiving training [AOR=1.59, 95%CI (1.06, 2.39) were factors significaantly associated with the level of knowledge regarding POP management.  Conclusion: This study indicated that the good level of knowledge towards POP management was poor. Educational level, working experience and receiving training were factors significantly associated with nurses' level of Knowledge towards POP management. Finally, we recommend that the training program for nurses concerning to the POP management guidelines and treatment protocols should be designed to improve their knowledge. Further, health education program for nurses may be necessary to take place.